Pengaruh Orientasi Pasar, Orientasi Pembelajaran dan Inovasi Produk terhadap Kinerja Pemasaran - Zikriatul Ulya (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2019)
The purpose of this study is to examine and analyze the eff ect of market orientation, learning orientation and product innovation of marketing performance. This study use a descriptive quantitative approach, and collected data through questionnaire. The sample used was 84 small industry of pisang sale in Aceh Timur Distric – Aceh. The data analysis tool used is classic asumption method with multiple linear regression analysis, coeffi cient of determination, F test and t test. The result of study are as follows: (1) Market orientation have a signifi cant positive eff ect of marketing performace indicate by the market orientation coeffi cient (X1) which is positive, namely 6.785, and the p-value less than the signifi cance level (0.000 < 0.005). (2) Learning orientation have a signifi cant positive eff ect of marketing performance, indicate by the learning orientation coeffi cient (X2) which is positive, namely 2.249, and the p-value less than the signifi cance level (0.027 < 0.005). (3) Innovation product have a signifi cant positive eff ect of marketing performance, indicate by the innovation product coeffi cient (X2) which is positive, namely 2343, and the p-value less than the significance level (0.022 < 0.005). (4) Market orieas an agregrat htation, learning orientation and innovation product have a signifi cant eff ect of marketing performance, indicated by the probability valeu of F less than the signifi cance level (0.000 < 0.05). The coeffi cient of determination (R2) is 0.621 or 62,1%. This indicate that 62,1% of marketing performance is aff ected by market orientation, learning orientation and innovation product while remaining 37,9% is aff ected by other independent variables not under study.